1, 2‐Diacylglycerol choline phosphotransferase catalyzes the final step in the unique Treponema denticola phosphatidylcholine biosynthesis pathway. Issue 5 (17th January 2017) - Vences‐Guzmán, Miguel Ángel; Paula Goetting‐Minesky, M.; Guan, Ziqiang; Castillo‐Ramirez, Santiago; Córdoba‐Castro, Luz América; López‐Lara, Isabel M.; Geiger, Otto; Sohlenkamp, Christian; Christopher Fenno, J.
Summary: Treponema denticola synthesizes phosphatidylcholine through a licCA ‐dependent CDP‐choline pathway identified only in the genus Treponema . However, the mechanism of conversion of CDP‐choline to phosphatidylcholine remained unclear. We report here characterization of TDE0021 (herein designated cpt ) encoding a 1, 2‐diacylglycerol choline phosphotransferase homologous to choline phosphotransferases that catalyze the final step of the highly conserved Kennedy pathway for phosphatidylcholine synthesis in eukaryotes. T. denticola Cpt catalyzed in vitro phosphatidylcholine formation from CDP‐choline and diacylglycerol, and full activity required divalent manganese. Allelic replacement mutagenesis of cpt in T. denticola resulted in abrogation of phosphatidylcholine synthesis. T. denticola Cpt complemented a Saccharomyces cerevisiae CPT1 mutant, and expression of the entire T. denticola LicCA‐Cpt pathway in E. coli resulted in phosphatidylcholine biosynthesis. Our findings show that T. denticola possesses a unique phosphatidylcholine synthesis pathway combining conserved prokaryotic choline kinase and CTP:phosphocholine cytidylyltransferase activities with a 1, 2‐diacylglycerol choline phosphotransferase that is common in eukaryotes. Other than in a subset of mammalian host‐associated Treponema that includes T. pallidum, this pathway is found in neither bacteria nor Archaea. Molecular dating analysis of the Cpt gene family suggests that a horizontal gene transfer event introduced this gene into an ancestral Treponema well after its divergence from other spirochetes. Abstract : Some members of genus Treponema synthesize phosphatidylcholine via CDP‐choline, which other bacteria utilize for phosphorylcholine modification of cell‐surface structures. Outside this subset of host‐associated spirochetes that includes T. denticola and T. palladium, this membrane phospholipid synthesis pathway is found only in Eukaryota. The Treponema gene encoding the last enzymatic step (1, 2‐diacylglycerol choline phosphotransferase) was likely acquired by horizontal transfer from a eukaryotic organism into an ancestral Treponema well after its divergence from other spirochetes.